2016
DOI: 10.1161/jaha.116.003759
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus‐Productive Infection Is Associated With Acute Coronary Syndrome

Abstract: BackgroundAlthough an association between human herpesvirus (HHV) infection and atherosclerosis has been suggested, the data supporting such an association are controversial and, in most cases, are based on serological evidence or on the presence of cell‐associated HHV DNA, which do not report about actual viral replication. We quantified the DNA of all 8 types of HHVs in plasma, in which their presence is evidence of viral replication.Methods and ResultsUsing quantitative real‐time polymerase chain reaction, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 63 publications
1
42
0
2
Order By: Relevance
“…Moreover, in that work we also found a positive correlation between the cytomegaloviral DNA load and T-lymphocyte differentiation within the atherosclerotic plaques of patients with cardiovascular diseases. 16 This result is in agreement with the studies on differentiation status of effector T lymphocytes in blood of patients infected with cytomegalovirus. 19,20,38−40 Here, we showed that the presence of cytomegaloviral DNA in plasma of patients with STEMI was significantly higher than in volunteers without cardiovascular diseases.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, in that work we also found a positive correlation between the cytomegaloviral DNA load and T-lymphocyte differentiation within the atherosclerotic plaques of patients with cardiovascular diseases. 16 This result is in agreement with the studies on differentiation status of effector T lymphocytes in blood of patients infected with cytomegalovirus. 19,20,38−40 Here, we showed that the presence of cytomegaloviral DNA in plasma of patients with STEMI was significantly higher than in volunteers without cardiovascular diseases.…”
Section: Discussionsupporting
confidence: 91%
“…12−14 At the same time, investigation of a productive cytomegalovirus infection by viral DNA in blood plasma and viral RNA in peripheral blood mononuclear cells found a strong positive correlation to the development of acute coronary syndrome. 15,16 In the current study, we investigated the mechanisms of impact of cytomegalovirus on a major atherosclerotic complication, ST-elevation myocardial infarction (STEMI). Previously in in vitro studies it had been shown that cytomegalovirus infects endothelial cells and activates T-lymphocyte migration into plaques, causing endothelial dysfunction, 17−20 which worsens the cardiovascular prognosis of patients with STEMI.…”
Section: Introductionmentioning
confidence: 99%
“…For example, researchers have detected cytomegalovirus DNA in atherosclerotic plaques, and the presence of cytomegalovirus has been correlated with restenosis in patients who have undergone coronary atherectomy or angioplasty . Other studies found the level of serum cytomegalovirus DNA was higher in patients with stable coronary artery disease and acute coronary syndrome than in healthy controls; cytomegalovirus IgG seropositivity was associated with future risk of stroke after adjusting for other risk factors . Furthermore, there is growing evidence implying an important role of this virus in vascular pathology by introducing slow but persistent inflammation in the vessel wall …”
Section: Introductionmentioning
confidence: 99%
“…More recently, however, cells of various types, such as smooth muscle cells, macrophages, and T cells, have been found to play an important role in atherosclerotic plaque formation [2]. Moreover, a currently accepted theory of atherogenesis emphasizes the role of immune system activation caused by oxidized lipoproteins, which activate endothelial cells (as do other foreign agents within the vascular wall) [3,4]. It is thought that immune cells are attracted by chemokines, which are produced by activated endothelial cells, and migrate into the subendothelium, where they proliferate, leading to atherosclerotic plaque progression [2,57].…”
Section: Introductionmentioning
confidence: 99%